Performa Pertumbuhan Broiler Pasca Penghentian Antibiotic Growth Promoters (AGP) dalam Pakan Ternak Pola Kemitraan di Kabupaten Jember - A. F. Prasetyo; M. Y. M. Ulum; B. Prasetyo; J. I. Sanyoto (Jurnal Peternakan, 2020)
This research was to know the growth performance of broilers and feed consumption effect, life weight, weight gain (PBB), Feed Convertion Ratio (FCR), mortality, and age of harvesting against Performance Index (IP) In Sukowono District, Jember Regency. The results of multiple linear regression analyses were obtained the following equation Y = 419.70 – 86,369X1 + 312,347X2 – 12,001X3 – 47,132X4 + 5,440X5 – 9,608X6. T-test result indicates feed consumption variable, life weight, and harvest age affect IP, while weight gain variables, FCR, and mortality do not affect the IP. F-test result indicates the probability value of all independent variables (X) jointly affects the dependent variable (Y), with a coefficient of determination (R2) value of 0,998. Broiler growth performance shows that the average feed consumption, live weight, weekly weight gain, and harvest age decrease, while feed convertion ratio and mortality rate increase.